THE GENDER EQUALITY CAMPAIGN IN PICTURE STORY AL-BINTU MITSLUL WALAD (A ROLAND BARTHES’S SEMIOTICS STUDY) - Mamat Rachmat; Firstiyana Romadlon Ash Shidiqiyah; Ahmad Syakir Maulana (Arabic Literature Department, 2023)
The picture story